Faded Bedtime Intervention for Delayed Sleep Onset in an Adolescent With Autism Spectrum Disorder. (June 2020) - Luiselli, James K.; Harper, Jill M.; Shlesinger, Andrew; Murphy, Kerrianne J.; Luke, Katherine
We report the case of an 18-year-old girl who had autism spectrum disorder (ASD) and demonstrated persistent delayed sleep onset after going to bed in her group home at a residential school. Intervention consisted of a faded bedtime in which her customary time to bed was extended later into the night, then gradually made earlier as she started falling asleep more rapidly over the course of many weeks. By conclusion of the study and at a 1-month follow-up, the girl was falling asleep in less than 30 min after going to bed and sleeping an average of 8.4 hr each night. Compared with previous research with children in inpatient and home environments, the study found positive effects from a faded bedtime intervention without additional procedures, targeted an adolescent with ASD, and was conducted by care providers in a novel residence setting.